2021
DOI: 10.3389/fmicb.2021.706700
|View full text |Cite
|
Sign up to set email alerts
|

Virulent Drexlervirial Bacteriophage MSK, Morphological and Genome Resemblance With Rtp Bacteriophage Inhibits the Multidrug-Resistant Bacteria

Abstract: Phage-host interactions are likely to have the most critical aspect of phage biology. Phages are the most abundant and ubiquitous infectious acellular entities in the biosphere, where their presence remains elusive. Here, the novel Escherichia coli lytic bacteriophage, named MSK, was isolated from the lysed culture of E. coli C (phix174 host). The genome of phage MSK was sequenced, comprising 45,053 bp with 44.8% G + C composition. In total, 73 open reading frames (ORFs) were predicted, out of which 24 showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Whole genome sequence and proteomic analysis of ES10 phage showed that ES10 phage is the member of Drexlerviridae. MSK bacteriophage effective against E. coli belonging to Drexlerviradae family was reported previously (Khan et al, 2021). Transmission electron microscopy of ES10 phage revealed that ES10 is tailed phage with icosahedral head.…”
Section: Discussionmentioning
confidence: 56%
“…Whole genome sequence and proteomic analysis of ES10 phage showed that ES10 phage is the member of Drexlerviridae. MSK bacteriophage effective against E. coli belonging to Drexlerviradae family was reported previously (Khan et al, 2021). Transmission electron microscopy of ES10 phage revealed that ES10 is tailed phage with icosahedral head.…”
Section: Discussionmentioning
confidence: 56%
“…MegaX software was used to align the AtGLRs and BnGLRs by applying the clustal W function. For the construction of a phylogenetic tree in Mega X (v10.2.2) [ 35 ], the maximum likelihood (ML) algorithm with 1000 bootstrap replicates and partial deletion (95% site coverage as cut-off) were used for gaps and missing data. Based on their sequence similarity with AtGLRs in the phylogenetic tree, the members of the BnGLR family were named.…”
Section: Methodsmentioning
confidence: 99%